Utilizing nonpolar organic solvents for the deposition of metal-halide perovskite films and the realization of organic semiconductor/perovskite composite photovoltaics - Noel, NK; Wenger, B; Habisreutinger, SN; Snaith, HJ (American Chemical Society, 2022)
Having captivated the research community with simple fabrication processes and staggering device efficiencies, perovskite-based optoelectronics are already on the way to commercialization. However, one potential obstacle to this commercialization is the almost exclusive use of toxic, highly coordinating, high boiling point solvents to make perovskite precursor inks. Herein, we demonstrate that nonpolar organic solvents, such as toluene, can be combined with butylamine to form an effective solvent for alkylammonium-based perovskites. Beyond providing broader solvent choice, our finding opens the possibility of blending perovskite inks with a wide range of previously incompatible materials, such as organic molecules, polymers, nanocrystals, and structure-directing agents. As a demonstration, using this solvent, we blend the perovskite ink with 6,6-phenyl-C-61-butyric acid methyl ester and show improved perovskite crystallization and device efficiencies. This processing route may enable a myriad of new possibilities for tuning the active layers in efficient photovoltaics, light-emitting diodes, and other semiconductor devices.